Does Financial Inclusion Enhance Indonesia's First Demographic Dividend? - I Gede Putu Dharma Yusa; Aziz Wahyu Suprayitno; Faiz Abdullah Wafi (Universitas Negeri Semarang, 2025)
This study examines whether financial inclusion enhances the first demographic dividend in Indonesia. Using a household-level approach, we measure the first demographic dividend through the economic support ratio and per capita expenditure, while financial inclusion is assessed based on savings account ownership in formal financial institutions. The research utilizes data from the 2022 National Socio-Economic Survey (Susenas) and applies a multiple linear regression model estimated via the Ordinary Least Squares (OLS) method. Empirical findings indicate that financial inclusion and the economic support ratio significantly enhance the first demographic dividend, as reflected in increased per capita expenditure. However, nearly one-third of households still lack access to formal financial institutions, with evidence suggesting a concentration of savings account ownership within specific households. Subsample analysis underscores the need to optimize the demographic dividend through financial inclusion, particularly for households headed by females, those engaged in agriculture and the informal sector, poor households, and those in rural areas and outside Java. Therefore, we recommend that the financial industry expand its services beyond its current target market and proactively tailor financial products to meet the diverse needs of the Indonesian population.